Microwave Assisted Essential Oil Analysis and Antimicrobial Activity of M. alpestris subsp. alpestris - Beyza Cansu, Tayyibe; Yucel, Murat; Sinek, Kadriye; Baltaci, Cemalettin; Alpay Karaoglu, Sengul; Yayli, Nurettin (Asian Journal of Chemistry, 2010)
The present work describes the chemical composition and antimicrobial activity of the essential oil of Myosotis alpestris F.W. Schmidt subsp. alpestris (Boraginaceae). The essential oil wasn-nonanal (11.8 %), decanal (10.8 %), noctanalo-cymene (3.9 %), tetradecanal (3.7 %),β-farnesene (2.0 %). The isolated essential oils of M. alpestris subsp. alpestris pseudotuberculosis was tested for antimicrobial activity against the bacteria Escherichia coli, Yersinia, Pseudomonas aeruginosa, Staphylococcus aureus, Enterococcus faecalis, Listeria monocytogenes albicans 1000 μg/mL and they showed only antibacterial activity against fungus bacteria. , Bacillus cereus, Mycobacterium smegmatis and the fungus Candidaand Saccharomyces cerevisiae at maximum essential oil concentration in hexane of obtained from all parts of the plant by microwave distillation and analyzed by GC-FID and GCMS. Forty-seven components representing 88.2 % of the total oil were characterized and the main components of this species were found to be (10.7 %), hexahydrofanesyl acetone (6.6 %), eicosanol (2.2 %) and E-